Rivaroxaban Plus Aspirin in Patients With Vascular Disease and Renal Dysfunction From the COMPASS Trial - Fox K.A.A.; Eikelboom J.W.; Shestakovska O.; Connolly S.J.; Metsärinne K.P.; Yusuf S. (ELSEVIER SCIENCE INC, 2022)
BACKGROUND: Chronic kidney disease is associated with an increased risk of both bleeding and ischemic cardiovascular events.
OBJECTIVE: The purpose of this study was to determine the balance of risks and benefits from the dual pathway antithrombotic regimen (rivaroxaban 2.5 mg twice daily [bd] plus aspirin, compared with aspirin) in vascular patients with or without moderate renal dysfunction.
METHODS: This was a secondary analysis of the COMPASS (Cardiovascular OutcoMes for People using Anticoagulation StrategieS) trial involving 27,395 patients with chronic coronary or peripheral artery disease.
RESULTS: In COMPASS, 21,111 patients had an estimated glomerular filtration rate (GFR) at baseline of >= 60 ml/min, 6,276 had a GRF of <60 ml/min. Both the primary efficacy outcome (cardiovascular death, myocardial infarction, or stroke) and major bleeding were more frequent in those with renal dysfunction, and the frequency of these outcome events was inversely related to GFR. However, the primary outcome was consistently reduced with rivaroxaban 2.5 mg bd plus aspirin, irrespective of GFR category (GFR >= 60 ml/min, 3.5% rivaroxaban plus aspirin, 4.5% aspirin alone, hazard ratio [HR]: 0.76, 95% confidence interval [CI]: 0.64 to 0.90; GFR <60 ml/min, 6.4% rivaroxaban plus aspirin, 8.4% aspirin alone, HR: 0.75; 95% CI: 0.60 to 0.94). Major bleeding was more frequent with rivaroxaban 2.5 mg plus aspirin versus aspirin alone in those with GFR >= 60 ml/min (2.9% rivaroxaban plus aspirin, 1.6% aspirin alone, HR: 1.81; 95% CI: 1.44 to 2.28) and similarly in those with GFR <60 ml/min (3.9% rivaroxaban plus aspirin, 2.7% aspirin alone, HR: 1.47, 95% CI: 1.05 to 2.07).CONCLUSIONS The benefits of the dual pathway COMPASS regimen (rivaroxaban 2.5 mg bd plus aspirin), versus aspirin alone, are preserved in patients with moderate renal dysfunction without evidence of an excess hazard of bleeding.